THE UKRAINIAN-POLISH PARTNERSHIP IN THE SECURITY SYSTEM OF EAST-CENTRAL EUROPE IN THE POLITICAL THOUGHT OF BOHDAN OSADCHUK - Лодин, П. З. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the model of regional security system of East-Central Europe in the B.Osadchuk’s political thought, with its different configurations in the period to the end of the XX century. A key role in this system played an Ukrainian-Polish partnership, so it was important to establish reconciliation between both parties for its implementation. Ukrainian journalist’s point of view on the problem field is represented in a form of model, that is systematized by periods.